Impact of tumour budding grade in 310 patients who underwent surgical resection for extrahepatic cholangiocarcinoma. Issue 6 (20th March 2019) - Ogino, Mariko; Nakanishi, Yoshitsugu; Mitsuhashi, Tomoko; Hatanaka, Yutaka; Amano, Toraji; Marukawa, Katsuji; Nitta, Takeo; Ueno, Takashi; Ono, Masato; Kuwabara, Shota; Yamada, Tooru; Hirano, Satoshi
Abstract : Aims: Tumour budding is a risk factor for poor prognosis in various cancers. Tumour buds may present an epithelial–mesenchymal transition (EMT) morphological phenotype. This study aimed to elucidate the prognostic impact of tumour budding grade and its association with clinicopathological and EMT‐related features in perihilar cholangiocarcinoma (PHCC) or distal cholangiocarcinoma (DCC). Methods and results: Subjects included 195 PHCC and 115 DCC patients. The numbers of tumour buds in different patients were stratified for postoperative survival using the recursive partitioning technique. Consequently, the numbers of tumour buds in PHCC patients were classified into three grades; namely, low (0–4 buds); intermediate (5–11 buds); and high (≥12 buds); those of DCC patients were classified into two grades; namely, low (0–4 buds) and high (≥5 buds). In both PHCC and DCC patients, high tumour budding grade was associated with poor histological differentiation, higher pT factor, presence of lymphatic, venous, perineural invasion and regional lymph node metastasis. In PHCC patients, residual invasive tumour in the resected margin was also associated with high tumour budding grade. For both PHCC and DCC patients, high tumour budding grade was an independent adverse prognostic factor in multivariate analysis ( P  < 0001 and P  = 0.046, respectively). Immunohistochemical examination revealed that the number of tumour buds increased in patients with tumours showing a mesenchymal profile (negative for E‐cadherin and positive for vimentin). Conclusions: Higher tumour budding grade is associated with invasive clinicopathological features, adverse postoperative prognosis and EMT status in extrahepatic cholangiocarcinoma.